The Geoinformation Support of the Landscapes Spatial Development - Makieieva, Liudmyla; Sadovyy, Ivan; Mokierova, Nataliia; Tymoshevskyi, Vladyslav (International Journal of Engineering and Technology, 2018)
Under current conditions the progressively increasing anthropogenic pressure on land resources and significant changes in the structure of land tenure require the creation and immediate implementation of a system for surveillance and inspection the use and condition of lands in order to identify changes on-time, to asses them prevent and eliminate the consequences of negative processes occurring on the land tenure territory. The task of effective use of land is not properly performed due to the lack of reliable information about its condition and use. Such information can be obtained through the creation and operation of the ongoing system of the land condition state monitoring based on geoinformation technologies. This study is directed at determining the influence and correlation of the landscape spatial development with elements of the territory organization using the criterion of agricultural crops productivity with geographic information system (GIS).Â The necessity of the analysis is connected with the detection of cyclicality, regularity, the influence direction of the territory organization elements on the landscape spatial development, which will make it possible to apply the most cost-effective and environmentally sound ways of using particular areas.Â Â Â